Femoral head and liner exchange in patients with atraumatic dislocation: results of a retrospective study with 6 years follow-up - Hanslmeier, Maximilian G.; Maier, Michael Wolfgang; Feißt, Manuel; Beckmann, Nicholas A. (Medicina, 2021)
Background and Objectives: Femoral head and liner exchange is an established treatment for polyethylene wear but has had a more limited role in the treatment of other conditions including dislocation, because of concerns about an increased postoperative dislocation rate. Some authors have considered dislocation associated with polyethylene wear to be a contraindication for this procedure. Materials and Methods: Our retrospective review evaluated the outcome of head and liner exchange in a small consecutively operated heterogeneous cohort of 20 patients who presented with dislocation unrelated to trauma, component malposition or component loosening. Of this group, 12 had prior primary total hip arthroplasty, and 8 had prior revision total hip arthroplasty, and included 4 patients with prior revision for dislocation. Mean follow-up was 6 ± 3.5 years (range 1-145 months). Results: Kaplan-Meier analysis revealed a revision-free implant survival from any cause of 80% (confidence interval 95%:64.3-99.6%) at 5 years after head and liner exchange (index surgery). At final follow-up, 83.3% of patients (n = 10) with prior primary total hip arthroplasty and 62.5% of patients (n = 5) with prior revision total hip arthroplasty, had not required subsequent revision for any cause. None (0%) of the primary total hip arthroplasty group and 3 (38%) of the revision arthroplasty group had required revision for further dislocation. Of the eight revision arthroplasty patients, four had a prior revision for dislocation and three of these four patients required further revision for dislocation after index surgery. The fourth patient had no dislocation after index surgery. One additional patient who had prior revision surgery for femoral component fracture suffered dislocation after index surgery, but was successfully treated with closed reduction. Conclusions: In our study population, femoral head and liner exchange was an effective treatment option for patients with prior primary total hip arthroplasty and also for a highly select group of revision total arthroplasty patients with no prior history of dislocation. Femoral head and liner exchange does not appear to be a viable treatment option for patients who have had revision total arthroplasty after prior dislocations.
Gesehen am 17.12.2021